2009
DOI: 10.1097/scs.0b013e3181b176b2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen

Abstract: Osseointegration was an innovative treatment in dentistry during the last 3 decades. The success of osseointegration is related to factors such as material biocompatibility, adequate quality of bone tissue that allows implantation, surgical technique, and macrostructure and microstructure of implant. The osseointegrated implants are successfully applied in dental clinic including oral and facial rehabilitations mainly for patients submitted to mutilating surgeries. However, patients submitted to radiation ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In Oral and Maxillofacial surgery, HBOT is mainly used to prevent or to treat radiotherapy associated osteonecrosis of the jaws 16. In addition, this treatment modality has been found successful in increasing the incorporation rate of autogenous bone grafts 17 and soft tissue flaps 18, as well as dental implant success rates 19 in the irradiated mandible.…”
Section: Introductionmentioning
confidence: 99%
“…In Oral and Maxillofacial surgery, HBOT is mainly used to prevent or to treat radiotherapy associated osteonecrosis of the jaws 16. In addition, this treatment modality has been found successful in increasing the incorporation rate of autogenous bone grafts 17 and soft tissue flaps 18, as well as dental implant success rates 19 in the irradiated mandible.…”
Section: Introductionmentioning
confidence: 99%
“…If the patient does not meet all of the following standards, HBOT is an advised treatment. HBOT prepares the bone and the adjacent tissue for implant retrieval 48…”
Section: Uses In Dentistrymentioning
confidence: 99%
“…9,10,13 Patients with a history of radiation therapy have a greater risk of failed implant osseointegration and osteoradionecrosis related to reduced tissue perfusion and decreased bone integrity. 9,10,50,77,78…”
Section: Discussionmentioning
confidence: 99%
“…9,10,13 Patients with a history of radiation therapy have a greater risk of failed implant osseointegration and osteoradionecrosis related to reduced tissue perfusion and decreased bone integrity. 9,10,50,77,78 In contrast, Curi et al reported a 100% survival rate of orbital implants at 2 years, which may be related to placing implants in the cortical bone of the orbital rim. 10 Curi et al also noted a lower 2-year survival of nasal implants, which may be attributed to placing the implants in the less compact bone of the maxilla.…”
Section: Long-term Outcomes Of Facial Prosthesesmentioning
confidence: 98%